Why do older adults hesitate to get the flu vaccine? A cross-sectional study on vaccine hesitancy in the post-COVID-19 era - Xinyue Wang; Sanmei Wen; Jiaqian Wu; Ziyi Cui; Hong Shen; Shiyao Hu; Shujun Zeng; Yan Tang (Frontiers in Public Health, 2025)
ObjectivesTo investigate the determinants of influenza vaccine hesitancy (VH) among older adults in Shanghai, China, using the 3Cs model (confidence, complacency, and convenience) and vaccine literacy (VL) framework. This study also explored the potential effect of COVID-19 vaccine hesitancy on influenza vaccine attitudes in the post-COVID-19 era.MethodsWe conducted a community-based cross-sectional study from January to June 2024 in Shanghai, China, involving 1,300 adults aged ≥60 years. Participants were recruited through stratified random sampling. Inclusion criteria were: community-dwelling adults aged ≥60 years in Xuhui District. Multinomial logistic regression models were used to identify predictors of vaccine hesitancy, adjusting for sociodemographic variables, self-reported health status and self-report vaccination experiences. Structural equation modeling (SEM) was employed to examine the underlying factors contributing to vaccine hesitancy and quantify their interrelationships.ResultsA high proportion (85.2%) of participants exhibited influenza vaccine hesitancy, with 16.2% being complete refusers. Key predictors of hesitancy included distrust in vaccine efficacy (adjusted Odds Ratio [aOR] = 2.28 for refusal), low perceived influenza severity (aOR = 5.59 for refusal), and overreliance on non-pharmaceutical interventions (NPIs) (aOR = 3.37 for refusal) and influenza-specific medication (aOR = 3.76). Limited health communication with community health workers (CHWs) and low family support significantly amplified refusal risks (aOR = 3.63). Higher vaccine knowledge reduced hesitancy (aOR = 1.85), though paradoxically, higher critical vaccine literacy correlated with refusal tendencies (aOR = 0.36). Significant standardized estimated coefficient (β) were observed between confidence and complacency (β = 0.846), side-effect experience and complacency (β = 0.293), side-effect experience and depression (β = 0.294), convenience and depression (β = 0.293), and side-effect experience and needle phobia (β = 0.362).ConclusionVaccine confidence deficits and complacency regarding influenza severity are major drivers of hesitancy in older adults. This hesitancy is further exacerbated by COVID-19 vaccine skepticism and nuanced aspects of vaccine literacy. System-level interventions should integrate proactive vaccine counseling into routine care, strengthen family engagement in immunization decisions, and develop misinformation-resilient vaccine literacy programs specifically tailored for this vulnerable population.